COMMODITY SCIENCE AS A SCIENCE AND EDUCATIONAL DISCIPLINE: PRINCIPLES OF BUILDINGS AND DEVELOPMENT DIRECTIONS - Babukh, Ilona (Видавничий дім "Гельветика", 2017)
The analysis of commodity science as a science and educational discipline is carried out; the subject of commodity science is defined, those are consumer values and methods of their knowledge and its providing. The purpose of commodity science, as well as its task as a science and educational discipline for the achievement of this goal is singled out. The principles of constructing commodity science as a science and professional activity are revealed, they are safety, efficiency, compatibility, interchangeability and systematization, conformity. The main directions of commodity science development as a scientific and educational discipline in modern Ukraine are determined and summarized.
ТОВАРОЗНАВСТВО ЯК НАУКА ТА НАВЧАЛЬНА ДИСЦИПЛІНА: ПРИНЦИПИ ПОБУДОВИ ТА НАПРЯМКИ РОЗВИТКУ
Keywords: commodity; commodity science as a scientific discipline; commodity science as a discipline; subject of commodity science; principles of commodity science; directions of development of commodity science